168k views
2 votes
What are the solutions ?

7x ^(2) + 10x - 3 = x ^(2) + 3x


User Eydelber
by
5.7k points

1 Answer

3 votes

Answer:


x = ( - 3)/(2) \: or \: (1)/(3)

Explanation:


7 {x}^(2) + 10x - 3 = {x}^(2) + 3x


= > 7 {x}^(2) - {x}^(2) + 10x - 3x -3 = 0


= > 6 {x}^(2) + 7x - 3 = 0


= > 6 {x}^(2) + 9x - 2x - 3 = 0


= > 3x(2x + 3) - 1(2x + 3) = 0


= > (2x + 3)(3x - 1) = 0

Here x will have 2 values.

1)
2x + 3 = 0


= > 2x = - 3


= > x = ( - 3)/(2)

2)
3x - 1 = 0


= > 3x = 1


= > x = (1)/(3)

User Ashim
by
5.1k points